Gumbo for the soul III : males of color share their stories, meditations, affirmation, and inspirations - Wright, Brian L.; Bryan, Nathaniel (College teacher); Sewell, Christopher J. P.; Yates, Lucian, III; Robinson, Michael A. (Educator); Thomas, Kianga (Emerald Publishing Limited : Information Age Publishing, 2019)
This book for, about, and by Males of Color, amplifies triumphs and successes while documenting trials and tribulations that are instructive, inspiring, and praiseworthy. This book will be a must-read for every Male of Color.
Cover title.
Keywords: African American men -- Social life and customs -- Anecdotes.; African American men -- Social conditions -- Anecdotes.; African American men -- Biography -- Anecdotes.; Conduct of life -- Anecdotes.; African American men.; African American men -- Social conditions.; African American men -- Social life and customs.; Conduct of life.; elektronické knihy; Anecdotes.; Biographies.; Social Science -- Black Studies (Global); Ethnic studies.; Relating to people of the African diasporas, heritage.; electronic books